2003
DOI: 10.1086/377704
|View full text |Cite
|
Sign up to set email alerts
|

Observations of DG Tauri with the Keck Interferometer

Abstract: We present the first science results from the Keck Interferometer, a direct-detection infrared interferometer utilizing the two 10 m Keck telescopes. The instrument and system components are briefly described. We then present observations of the T Tauri object DG Tau, which is resolved by the interferometer. The resolved component has a radius of 0.12-0.24 AU, depending on the assumed stellar and extended component fluxes and the model geometry used. Possible origins and implications of the resolved emission a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 26 publications
2
25
0
Order By: Relevance
“…In both cases, the estimates may differ by more than three standard deviations. The additional errors atop the statistical errors determined by the data processing software are 3.3±1.2 % on the square visibilities (mean and dispersion in our 20 surveyed stars), which is in line with the generally accepted value of 5% (Colavita et al 2003). However, the purely systematic term (highly correlated errors) is only 1.8 ± 0.9 %.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…In both cases, the estimates may differ by more than three standard deviations. The additional errors atop the statistical errors determined by the data processing software are 3.3±1.2 % on the square visibilities (mean and dispersion in our 20 surveyed stars), which is in line with the generally accepted value of 5% (Colavita et al 2003). However, the purely systematic term (highly correlated errors) is only 1.8 ± 0.9 %.…”
Section: Resultssupporting
confidence: 87%
“…However, complete removal does not happen. Colavita et al (2003) measured ≈ 5% systematic errors on the calibrated squared visibility amplitudes at the Keck Interferometer by observing binaries of known orbital parameters. More recently, high-precision diameter measurements using sufficiently well resolved stars with CHARA (White et al 2018;Karovicova et al 2018) were shown to significantly differ (several σ and up to 15%) from values previously obtained from under-resolved interferometric observations, leading the authors to conclude that they were plagued with undiagnosed systematics.…”
Section: Introductionmentioning
confidence: 99%
“…The early compendium of sizes showed some puzzling results for T Tauri disks, too. Some T Tauri disk sizes were quite large compared to expectations based on the central star luminosities (e.g., Colavita et al, 2003;Eisner et al, 2005). In some cases, the accretion luminosity of the infalling material is comparable to the star's luminosity and must be included in the total central luminosity.…”
Section: Size-luminosity Diagrammentioning
confidence: 87%
“…But the amount and morphology of this 'inner' material bears on how such PMS binary systems interact with and accrete material from their circumbinary reservoir, and motivates study with the highest-resolution techniques available. Here we report on observations of DQ Tau with the Keck Interferometer (KI, Colavita et al 2003). These observations partially resolve the DQ Tau system, and allow us to model the system visual orbit based on the spectroscopic orbit by M1997.…”
Section: Introductionmentioning
confidence: 91%